Oesophageal involvement in 26 consecutive patients with mucous membrane pemphigoid. (1st October 2017) - Zehou, O.; Raynaud, J.‐J.; Le Roux‐Villet, C.; Alexandre, M.; Airinei, G.; Pascal, F.; Heller, M.; Lièvre, N.; Laroche, L.; Caux, F.; Benamouzig, R.; Prost‐Squarcioni, C.
Summary: Background: Oesophageal involvement of mucous membrane pemphigoid (MMP) has not yet been thoroughly described. Objectives: To characterize systematically the endoscopic lesions of a series of patients with oesophageal symptoms seen at a referral centre for autoimmune bullous diseases. Methods: Clinical, endoscopic and immunological findings of consecutively referred patients with MMP with oesophageal involvement, systemic and endoscopic treatments, and follow‐up are described. Results: Of 477 consecutive patients with MMP consulting between 2002 and 2012, 26 (5·4%) had symptomatic oesophageal involvement. Dysphagia, observed in 23 (88%) patients, was the most frequent symptom. Oesophageal symptoms could be the first sign of MMP. Patients with oesophageal involvement had a mean of three other involved sites. At initial oesophageal endoscopy, 17 of 26 patients had active lesions (intact bullae, erosions and/or erythema), 15 had stricture(s) and 12 had other cicatricial lesions. Systemic therapy alone achieved oesophageal symptom relief for five patients. Dilatation was combined with systemic therapy for 12 patients and was successful in nine; one perforation occurred. Conclusions: Symptomatic oesophageal involvement affected 5·4% of patients with MMP. Dermatologists and gastroenterologists should be aware of these mucocutaneous diseases and their oesophageal involvement, as it could lead to earlier diagnosis and better care. Oesophageal dilatation could be a therapeutic option for symptomatic stricture not relieved by optimized systemic therapy alone.